Sexual dysfunction in females with depression: a cross-sectional study - Krishnankutty Sreelakshmy; Rajmohan Velayudhan; Deepak Kuriakose; Rema Nair (Trends in Psychiatry and Psychotherapy)
Abstract Introduction Female sexual dysfunction (FSD) in depression albeit common is strikingly understudied. The condition, if addressed properly, can be readily cured, improving the quality of life of the patient. Methods A consecutive sample of drug-naïve married female patients with depression was assessed. Depression was diagnosed using the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I). Depression severity was assessed using the Hamilton Depression Rating Scale (HAM-D), and sexual dysfunction, the Female Sexual Function Index (FSFI). Results Sexual dysfunction was found in 90% of the patients in our study. Patients with medical comorbidities showed a significant decrease in the desire subset of the FSFI (Mann-Whitney U=11.0, p=0.009), however there was no significant association with other subsets. Patients who expressed passive death wishes had higher scores on all indicators of sexual function and a significantly higher score in the orgasm subset of the FSFI (Mann-Whitney U=11.0, p=0.009). Conclusion The study showed a high prevalence of FSD in depressed females regardless of type and severity of depression. Depression with medical comorbidities was associated with a significant decrease in desire. Patients who expressed passive death wishes showed improved sexual function and significantly better orgasm.